Steel Corrosion in Concrete : Fundamentals and civil engineering practice - Bentur, Arnon; Berke, Neal; Diamond, Sidney (Modern Concrete Technology, 2014)
"Poor durability of concrete is a major cause of problems in modern building and civil engineering structures in all countries: the annual cost of investigating and repairing deteriorating reinforced concrete structures runs into many millions of pounds. This book explains the fundamentals of the corrosion of steel in concrete. It is comprehensive and provides a basis for the practising engineer to design concrete structures which avoid the problem using modern concepts and specifications. A limited discussion of corrosion measurement and repairs is also provided."--Provided by publisher.